“Like oil and water”? Partnerships between visual art institutions and youth organisations - Sim, Nicola (2018)
This thesis interrogates partnership working between galleries and youth organisations involved in a four-year, Tate led programme called Circuit (2013-2017). This programme sought to build sustainable networks with youth organisations and services across England and Wales in order to ‘improve access and opportunities for harder to reach young people’ who may not otherwise engage with galleries and museums (Circuit, 2013a). Reflecting on the similarities and divergences that characterise practice in gallery education and youth work, this research untangles the historic barriers and tensions that have affected relationships between practitioners, organisations and the youth and visual art sectors. Mobilising Pierre Bourdieu’s theoretical framework, galleries and youth organisations are conceptualised as part of distinct ‘fields’, and their particular traditions, customs and internal contests are analysed. An exploration of the fields’ development under successive governments and changing policy priorities reveals that art organisations benefit from a greater affordance of agency and autonomy than youth organisations, which contributes to the uneven power dynamics that often exist in these cross-sector alliances. Reports from engagement with sector events also highlight how concepts of art and creativity frequently deviate between the fields. Through an ethnographic approach to the research context, participant observations and interviews produce data about Circuit’s programmatic decisions, and its efforts to shift problematic habitual practices. A series of in-depth site studies illustrate different ways for organisations to work together, as well as the challenges of collaboration in pressured political and economic circumstances. Cross-site analysis allows for further deliberation on the compatibility of Circuit’s wider peer-led programme agenda with the comparative agenda and practice of youth organisations. The ambition for young people to continue an independent relationship with the galleries’ programmes is shown to be hindered by a number of sometimes-misrecognised factors that unintentionally alienate certain communities of young people, particularly from working class backgrounds. The final stage of the analysis studies the identity, attitudes and positions of various youth sector agents working and participating within Circuit, and the specific ‘capital’ they bring to the temporary programmatic field. In discussing the implications for practice and research, this thesis asks whether (beyond programmes such as Circuit) it would be possible to establish a permanent collaborative or cooperative field between the youth and gallery sectors. I argue that this would only happen if a range of systemic changes were made, such as the development of national and regional structures to support integrated practice sharing; deeper engagement with the meaning and repercussions of partnership working; a determination to work collaboratively to address social urgencies facing young people, and a fundamental commitment to shift pervasive inequalities in the visual art sector.